Reconstruction of Specular Reflective Surfaces using Auto-Calibrating Deflectometry - Rapp, Holger H. (Schriftenreihe / Institut für Mess- und Regelungstechnik, Karlsruher Institut für Technologie, 2013)
This thesis discusses deflectometry as a reconstruction method for highly reflecting surfaces. It focuses on deflectometry alone and does not use other reconstruction techniques to supplement with additional data. It explains the measurement process and principle and provides a crash course into an efficient mathematical representation of the principles involved. Using this, it reformulates existing three-dimensional reconstructing methods, expands upon them and develops new ones.